Mechanistic insights on ionic liquid and poly(ionic liquid) solutions for CO2 capture and cycloaddition reactions - Raquel V. Barrulas; Rodrigo M. Barão; Carlos E.S. Bernardes; Marcileia Zanatta; Marta C. Corvo (Carbon Capture Science & Technology)
This study explores the potential of ionic liquids (ILs) and poly(ionic liquid)s (PILs) for CO2 capture and conversion. Using molecular dynamics simulations in DMSO solutions, we found that ILs and PILs exhibit similar CO2 sorption, with the ILs [BMIM][OAc] and [P4,4,4,4][OAc] showing the highest capacities. Bromide-derived PILs enhance aqueous sorption through cage formation, unlike ILs. We also examined the catalytic efficiency of PILs P[VBA]Cl and P[VBP]Cl, and IL [BA]Cl in CO2 cycloaddition reactions. DMSO decreases IL catalytic activity but improves P[VBA]Cl's performance. These findings suggest that higher CO2 sorption in ILs does not always correlate with better catalytic results. In conclusion, IL and PIL solutions in DMSO demonstrate significant potential for the effective modulation of material properties.